FORMAL AND INFORMAL POLITICAL PRACTICES IN MODERN RUSSIA - Victoria Vladimirovna Eremina (Вестник Северо-Кавказского федерального университета)
The political life of our country is actively developing, new kinds of its realization appear. In this con- text, the question of study and systematization of political practices becomes more urgent. Particular attention is given to the sharing of such practices in the formal and informal, and their interaction. If the formal political practices characterized by regulatory framework and approving laws, the informal guided by public opinion, conventional stereotypes, the use of lawless resources. At present, the last are gaining in popularity.